Principles of Resistance in Gharbi Mustafa’s What Comes with the Dust, Goes with the Wind - Ahmed, Khorsheed; Ameen, Hishryar; Ahmed, Kawyar (Humanities Journal of University of Zakho, 2021)
This paper examines the principles of resistance in Gharbi M. Mustafa’s novel titled What Comes with the Dust, Goes with the Wind (2017). It is mainly an attempt to focus on the inner and outer enegertic power to a person in the hard times and shows the major principles of resistance along with its significance for survival This study primarily provides an introduction to the research statement and problem of the study. Concerning the methodology, close reaidng is used as an approach to conduct the study, besides, it further deals with an introduction to the origins of the Yazidi people and religion. The second section of the paper introduces the critical overview, which summarizes the findings of a number of studies related to the sufferings of the Yazidis’ females during their captivity by several researchers. The central section provides the various forms of violence used against the Yazidis’ females and the impact of their wills and power, and their resistance to survive. In addition, the conclusion of the study concludes the findings of the research.